Superconducting Properties of MgB2 Bulk Shaped by Spark Plasma Sintering. (2016) - Noudem, J.G.; Dupont, L.; Gozzelino, L.; Bernstein, P.
Abstract: MgB2 bulk superconductors were shaped by Spark Plasma Sintering (SPS) process and the superconducting properties were measured. The obtained materials were 98% dense. Trapped field higher than 1.4 T was measured at 20 K. Otherwise, the possibility to use MgB2 for magnetic levitation has been investigated. The levitation force was investigated below 35 K. The results show that the SPS process allows to produce dense samples with enhanced superconductor characteristics as a result of improved grains connection and better densification of the bulk MgB2 superconductors, which could be a viable variant for magnetic levitation applications and/or as cryo-magnets.